Measuring fiscal spillovers in EMU and beyond: A global VAR approach - Ansgar Belke; Thomas Osowski (Research On Money in the Economy (ROME), 2016)
This paper identifies and measures fiscal spillovers in the EU countries empirically, using a structurally stable global vector autoregression (GVAR) model. For our purposes, the individual EU countries, as well as the most important international trading partners, are modelled with a special focus on the effects of either single-country or coordinated fiscal shocks such as increases in fiscal spending. Our aim is to look at the sign and the absolute values of fiscal spillovers in a country-wise perspective and at the time profile (impulse response) of the impacts of fiscal shocks. For this purpose, we differentiate between the spillovers of fiscal shocks in specific EMU member countries and the spillovers of 'regional' shocks, i.e. area-wide shocks to fiscal policy. Fiscal policy is measured by government expenditure, government revenues or the government budget balance, all as percentages of GDP. Special attention is paid to the question of whether or not spillovers are stronger within the EMU group than within the "Rest of Europe" due to tighter financial or trade links.
Keywords: C50; E61; F15; F42; H60; 330; EMU versus "Rest of Europe"; fiscal policy coordination; fiscal spillovers; GVAR analysis; regional shocks; impulse response analysis; trade weights